Association between advanced lung cancer inflammation index and chronic kidney disease: a cross-sectional study - Li, Xiaotong; Wang, Qian; Wu, Feng; Ye, Ziyang; Li, Yafeng (Frontiers in Nutrition, 2024)
Background Chronic kidney disease (CKD) is one of the common chronic diseases, and malnutrition and inflammation play a key role in the development of CKD. The advanced lung cancer inflammation index (ALI) is a novel index of nutrition and inflammation, and its association with CKD has not yet been clarified. The aim of this study was to explore the potential association between ALI and CKD. Methods We conducted a cross-sectional survey using data extracted from the National Health and Nutrition Examination Survey (NHANES, 2003–2018). Weighted multivariate logistic regression was used to assess the association between ALI and CKD, and smoothed curve fitting and threshold effect analyses were used to describe the nonlinear association between ALI and CKD. Subgroup analyses were performed to further assess the influence of other covariates on the relationship between ALI and CKD. Results A total of 39,469 adult participants were included in the study, of whom 7,204 (18.25%) were diagnosed with CKD. After adjusting for multiple confounders, we found a significant negative correlation between ALI and CKD (OR = 0.93; 95%CI, 0.91–0.95; p < 0.0001). The risk of CKD tended to decrease with increasing quartiles of ALI. Smoothed curve fitting showed an L-shaped negative correlation between ALI and CKD. Threshold analysis showed a saturation effect of ALI at the inflection point of 55.09. Subgroup analyses and interaction tests showed that this negative association was maintained across age, sex, race, BMI, diabetes, hypertension, cardiovascular disease, and cancer subgroups (P for interaction >0.05). Conclusion Our findings suggest a significant correlation between ALI and CKD in the US adult population. However, more large-scale prospective studies are still needed to further confirm our findings.